Applicability of three indices to evaluate the reproductive capacity of Rhipicephalus microplus engorged female ticks in acaricide efficacy trials - Sarli, Macarena (2023)
This study aimed to analyze the applicability of three different indices to evaluate the reproductive capacity of engorged females (RCEF). The indices, RCEF1, RCEF2 and RCEF3, were proposed as alternative to the count of the exact number of unhatched eggs and larvae in in vivo and in vitro acaricide efficacy trials that involve the use of engorged females to estimate the effect of a drug on their reproductive capacity. A comparison of the values of the reproductive efficiency index (REI) and the fertility efficiency index (FEI) of ten engorged females calculated from the count of the exact number of unhatched eggs and larvae and from the application of the proposed indices was performed. The absence of differences in the values obtained by both methods support the reliability and validate the use of the RCEF1, RCEF2 and RCEF3 indices to assess the RCEF.